Manajemen Perubahan Organisasi Sebagai Upaya Peningkatan Produktivitas Kerja di PT. Mayora Indah Tbk - Muhammad Gufron Shaff; Jumawan Jumawan; Hadita Hadita (Jurnal Bintang Manajemen, 2024)
Research Organizational change management is a process for managing changes carried out by an organization. Organizational change management can help organizations to increase work productivity by increasing employee skills and knowledge, employee training and development can increase employee abilities to carry out their duties and work better. This can increase employee work productivity because employees can complete their tasks and work more quickly and efficiently, increase employee motivation and commitment, employee motivation and commitment programs can increase employees' sense of belonging and pride in the company. This can increase employee motivation and commitment to work harder and produce better performance, improve the work environment, a comfortable and safe work environment can increase employee work productivity because employees can work more focused and efficiently. PT. Mayora Indah Tbk has implemented organizational change management effectively to increase the work productivity of its employees. These efforts have produced positive results. PT employee work productivity. Mayora Indah Tbk will increase by 20% in 2023. This is proven by an increase in added value per employee by 20%. Organizational change management as an effort to increase work productivity at PT. Mayora Indah Tbk: Stay focused on change goals, ensure support from leadership, effective communication, support from employees, evaluate success. By implementing these suggestions, PT. Mayora Indah Tbk can increase the effectiveness of organizational change management and achieve its goal of increasing employee work productivity.